White Privilege - Curran, Charles E. (Horizons, 2005)
This essay, an autobiographical narrative reflecting on my awareness of racism and white privilege in my theological journey, has not been an easy paper to write. In the last few years, I have become somewhat educated about racism and white privilege. I have to face the reality that I barely recognized the problem of racism in my own somewhat extensive writings and was blithely unaware of my own white privilege.The references to racism in my writings are very few, and there is never any concentrated discussion of the issue. This lack is especially telling in a moral theologian who often dealt with social ethics. Other theologians because of the focus of their discipline might not have the same opportunities to discuss and evaluate racism.In my 1982 monograph, American Catholic Social Ethics: Twentieth Century Approaches, I analyzed and critiqued the writings of five figures in Catholic social ethics. The index has seven references to race discrimination and racism. The two most extended discussions (at best, a few pages each) deal with Paul Hanly Furfey and John A. Ryan. Looking back now on what I wrote then, I am both embarrassed and uncomfortable.